Study of Solar Incidence on Roof Surface Geometry of Churches in San José de Cúcuta, Colombia: Analysis of Architectural Enclosure in Hot Weather (2024)
The geometry of architectural enclosures not only has direct impacts on the structural, spatial, and aesthetic aspects of the building but also influences thermal and, therefore, energy performance. Given the importance of energy efficiency in the construction sector, the main objective is to deepen the analysis of solar incidence on roof surfaces of three churches located in San José de Cúcuta, Colombia: Cathedral of San José de Cúcuta, the Church of Our Lady of Candelaria, and the Church of Our Lady of Carmen. The methodology is based on a structuralist approach in order to understand the relationship between the geometry of the surfaces and the solar incidence captured according to the shape. Thus, the research is divided into three stages: church selection, simulations of solar incidence, and analysis of the relationship between the geometry of the surfaces and the solar incidence obtained. The results indicate that the geometry of roof surfaces affects solar incidence. Furthermore, horizontal planes are prone to more solar exposure, while vertical planes register 9.70 up to 77.60 percent less solar incidence. In addition, folding and curved surfaces such as domes and inverted catenary curves reduce solar incidence by leaning toward vertical planes between 10 and 80 percent in contrast to flat roofs. Finally, the analysis of the relationship between surface geometry and solar incidence underscores the importance of carefully designing and orienting roof surfaces to optimize solar exposure and reduce the negative energy impact on buildings.